A Study on Knowledge Management and Knowledge Transfer - ABDULLA, AYESHA (2018)
This research is aimed to emphasize upon the Knowledge Management in organizations focusing on tangible concepts, methods and theories for knowledge transfer from experienced and expert employees to fresh UAE National graduates hired recently in private organizations in the UAE. The study identifies the gap in knowledge transfer techniques from already existing literature, providing relevant recommendations keeping in view the feasibility of their implementation in definite highlighting areas of concerns. Although a few researches have been made in this respect but still the detailed study is required in order to fulfill the research goal. This study reveals that the huge culture difference among the employees poses the cultural gap as the main challenge in the transfer of knowledge. Other important challenges and barriers emerged out of this study are: reluctance on part of experts to transfer their knowledge being protective of their knowledge and for the fear of job and position security, poor outdated traditional style of knowledge transfer without using the modern technology and restricting creativity and binding graduates to training rooms thus creating disinterest among them, discouraging innovative aptitude and easy going aptitude of graduates.